2022
DOI: 10.1186/s12978-021-01267-9
|View full text |Cite
|
Sign up to set email alerts
|

If fear of infertility restricts contraception use, what do we know about this fear? An examination in rural Ethiopia

Abstract: Background Ethiopia has made great progress toward reducing unmet need for family planning and increasing contraception use over the last decade. However, almost one-quarter of women still have an unmet need. The primary reason for non-use is “method-related health concerns” and, within this broad category, the belief that using contraception will cause infertility is common. This belief extends beyond Ethiopia to low-, middle-, and high-income countries across the world. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
6
5
0
Order By: Relevance
“…"A woman easily leaves the marriage if they don't have many children with the man" (FGD K5) This current nding correlates with the one study conducted in Ethiopia [41] which established that women feared using contraceptives because they believed they would become infertile leading to their husbands abandoning them. This is, however, different from the nding in the current study where men are the ones fearing that their wives would leave them for new men.…”
Section: Separation Of Couples and Single Motherssupporting
confidence: 55%
“…"A woman easily leaves the marriage if they don't have many children with the man" (FGD K5) This current nding correlates with the one study conducted in Ethiopia [41] which established that women feared using contraceptives because they believed they would become infertile leading to their husbands abandoning them. This is, however, different from the nding in the current study where men are the ones fearing that their wives would leave them for new men.…”
Section: Separation Of Couples and Single Motherssupporting
confidence: 55%
“…The protection of sperm chromatin from damage is achieved through the incorporation of N-tertbutyl hydroxylamine (NTBH) and SOD/catalase mimetics into the culture conditions. Because research has shown that the production of reactive oxygen species (ROS) increases with increasing incubation time, it is recommended that the incubation period between sperm and oocytes be as short as is practically possible [236]. The makeup of the medium that is used for in vitro fertilisation can have a significant impact on the state of the oocytes and embryos that are to be implanted before they are successfully fertilised (IVF).…”
Section: Antioxidants and Assisted Reproductive Technologiesmentioning
confidence: 99%
“…After being ejaculated, spermatozoa go through a sequence of processes, including capacitation, the acrosome response [242], and sperm-oocyte interactions [243], in which myo-Ins plays a part. In addition, research conducted by Calogero and colleagues has shown that taking myo-Ins is a risk-free supplement that has the ability to significantly restore normal levels of serum gonadotropins and inhibin B (a serum marker that evaluates the presence and function of testicular tissue [244], as well as increase the percentage of acrosome-reacted spermatozoa, the concentration of sperm, the total number of sperm, and progressive motility [245].…”
Section: Inositolsmentioning
confidence: 99%
“…Improved understanding of women’s beliefs about how contraception may affect their future fertility [14] , [15] is important in guiding patient-centered care that addresses women’s concerns. This knowledge is particularly relevant for programs in SSA, where use of contraception among those wishing to avoid pregnancy is often low, unintended pregnancies are common, and legal restrictions limit access to safe abortion, thereby hindering women’s ability to achieve their reproductive goals [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%